Physical-chemical characteristics of the ricotta cheese samples on sale in the local markets of Campinas City, SP, Brazil, and the compliance of the nutritional information on the labels assessment - Esper, Luciana M. R. (2007)
The Brazilian Regulation for industrial and sanitary inspection of animal by-products (RIISPOA-Brazil), establishes some identity and quality parameters for ricotta cheese, without defining important physical-chemical characteristics which could specifically classify the product better. The objective of this investigation was to evaluate the commercially available ricotta cheeses with respect to physicalchemical composition, and the conformity of the declared values on the “nutritional information” table in the label, with those found at official laboratory analyses, taking into account the requirements established by Resolution RDC nº 360/2003 of the Brazilian Regulatory Agency ANVISA as the reference. Forty five samples consisted of three batches of 15 different brands of ricotta cheese were collected, and the analysed parameters were moisture, fat contents, protein , salt content, ash, titratable acidity, and pH. These analyses showed a considerable variations on the diverse product constituents, and the majority of the nutritional information on the labels failed to comply with the legislation (> ±20% tolerance). This high variation on ricotta cheeses physical-chemical composition might probably be associated with the diversity of alternative technologies used by the different manufacturers. These results indicated the need in establishing well-defined identity and quality standards aiming at product quality control and consumer safety improvement.